Evaluation of a suitable material for soft actuator through experiments and fe simulations - Natarajan, Elango; Muhammad Razif, Muhammad Rusydi; M Faudzi, AA; K., Palanikumar (IGI Global, 2020)
Soft actuators are generally built to achieve extension, contraction, curling, or bending motions needed for robotic or medical applications. It is prepared with a cylindrical tube, braided with fibers that restrict the radial motion and produce the extension, contraction, or bending. The actuation is achieved through the input of compressed air with a different pressure. The stiffness of the materials controls the magnitude of the actuation. In the present study, Silastic-P1 silicone RTV and multi-wall carbon nanotubes (MWCNT) with reinforced silicone are considered for the evaluation. The dumbbell samples are prepared from both materials as per ASTM D412-06a (ISO 37) standard and their corresponding tensile strength, elongation at break, and tensile modulus are measured. The Ogden nonlinear material constants of respective materials are estimated and used further in the finite element analysis of extension, contraction, and bending soft actuators. It is observed that silicone RTV is better in high strain and fast response, whereas, silicone/MWCNT is better at achieving high actuation.